Cultural influences on the fertility behaviour of first- and second-generation immigrants in Germany - Mustafa Yeter; Holger Stichnoth (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Using an epidemiological approach, we study the cultural influence on fertility outcomes of first- and second-generation female immigrants based on a 1% sample of the German population. We proxy for culture in the country of origin using total fertility rates from the year of migration, survey measures of fertility norms and cohort fertility rates from the year of birth. The last measure has not been used in the literature before. The large dataset allows us to focus on a relatively narrow range for age at migration and to estimate models that rely on within-country variation only, leading to more credible identification. We find a statistically significant, sizeable and robust impact of country-of-origin fertility rates on fertility outcomes. The impact works mainly through the intensive margin and less through the probability of having children. It is strongest in the first generation and becomes weaker for generation 1.5 (migrants arriving as children) and the second generation. The cultural influence is strongest for women with low education.
Keywords: J13; J16; J15; 330